Sealing strip coating material as well as preparation method and application thereof
By using polyethylene resin and other materials in the seal strip coating material for grafting and crosslinking vulcanization reaction, combined with the dynamic vulcanization process, the problem of melting and deformation of the seal strip coating during high-temperature bonding is solved, and the sealing of the seal strip is improved and heat resistance reduce the friction coefficient.
Patent Information
- Application Number
- CN202411482925.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing sealing strip coating materials are prone to melt and deform during high-temperature bonding, affecting the appearance and sealing properties of the sealing strips. The static friction coefficient and dynamic friction coefficient are high, resulting in poor sealing effect.
The grafting and crosslinking vulcanization reaction is carried out using polyethylene resin, silane coupling agent, initiator, antioxidant, liquid additive masterbatch, nano zinc oxide and catalyst to prepare a sealing strip coating with dispersed phase and continuous phase structure. The layer material can improve the crosslinking degree through dynamic vulcanization process and undergo chemical reactions in a high-temperature environment to enhance heat resistance.
The friction coefficient on the surface of the sealing strip is significantly reduced, the heat resistance, mechanical properties and corrosion resistance of the sealing strip are improved, the sealing effect is improved, and the melting deformation of the coating at the joint corner is avoided.
Smart Images

Figure CN119161770A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high molecular polyethylene materials, and in particular to a sealing strip coating material and a preparation method and application thereof. Background Art
[0002] In the automotive window sealing system, the main materials of the sealing strip include ethylene propylene diene monomer rubber (EPDM) and thermoplastic vulcanized rubber (TPV). Compared with TPV materials, the advantages of EPDM materials are mainly reflected in good resilience and compression permanent deformation, so EPDM sealing strips have better sealing properties. In the performance study of three friction layers named EPDM automotive glass guide groove sealing strips, authors Wang Haijun and Yang Fen also mentioned that EPDM has excellent comprehensive performance, excellent aging resistance, UV resistance, high and low temperature resistance, outstanding acid and alkali resistance, strong environmental adaptability, excellent elasticity and resistance to permanent deformation. At present, rubber automotive glass guide groove sealing strips are used more as base materials. In order to improve the fit between the sealing strip and the window glass, reduce the friction coefficient, and improve the sealing effect, the surface of the sealing strip often needs to be composite extruded with a low friction coefficient coating material. There are mainly two types of coating material selection, namely modified polyethylene material and TPV material, both of which are widely used in TPV material sealing strips. They are both thermoplastic materials with a melting point between 150-160℃. However, for EPDM sealing strips, there are certain limitations in the post-process (sealing strip corner joint). EPDM joints often require higher material and mold temperatures to ensure good joint strength. Usually, the molten temperature of the corner material can reach 260°C. After contacting with modified polyethylene or TPV coating materials, the coating material will melt and deform slightly due to heat, affecting the appearance and sealing of the sealing strip.
[0003] KR100644256B1 discloses a coating material for automobile sealing strips and a method for manufacturing the same. More specifically, relative to the total weight of the resin composition as the main component, (a) HDPE (high density polyethylene) 20-80% by weight is 300,000 or more, (b) HDPE (Mw) 150,000 to 250,000 with an average molecular weight of 80-20 is prepared by preparing a polyethylene resin composition containing 0.05 to 1.0 parts by weight, and (c) 0.05 to 1.0 parts by weight of a cross-linking agent and 0.05 to 1.0 parts by weight of a reactant terminator relative to 100 parts by weight of the main component, and by reaction extrusion, a coating material suitable for various shapes and uses is provided at a low cost. The material itself is still a thermoplastic material, and the above-mentioned limitations still exist in the process of high-temperature bonding of the sealing strip.
[0004] Based on the above-mentioned existing technologies, there are technical problems in the existing technologies that need to be solved urgently, such as the sealing strip or the sealing strip coating being melted and deformed due to heat during the high-temperature joining process, the surface flatness changing, thereby affecting the appearance and sealing of the sealing strip, and the high static friction coefficient or high dynamic friction coefficient in the surface friction coefficient. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a sealing strip coating material, wherein the raw materials for preparing the sealing strip coating material include polyethylene resin, silane coupling agent, initiator, antioxidant, liquid auxiliary agent masterbatch, nano zinc oxide, catalyst, and stearic acid, and a grafting and / or crosslinking vulcanization reaction is performed to prepare the sealing strip coating material; The sealing strip coating material comprises a grafted and cross-linked vulcanized polyethylene composition as a dispersed phase, and a grafted and uncross-linked vulcanized polyethylene composition as a continuous phase; The sealing strip coating material has a crosslinking degree of 50.2-56.3%, a static friction coefficient of 0.16-0.29, a dynamic friction coefficient of 0.14-0.25, a tensile strength of 24.7-26.8 MPa, a Vicat softening point of 124.3-127.9° C., and a Shore hardness of 61.4-61.9D.
[0006] Further, the crosslinking degree is tested according to GB / T 18474-2001, and the test environment conditions are: 23°C, 50%RH (relative humidity); The dynamic friction coefficient is tested according to GB / T 21282-2007, and the test environment conditions are: 23°C, 50%RH; The static friction coefficient is tested according to GB / T 21282-2007, and the test environment conditions are: 23°C, 50%RH; The tensile strength is tested according to GB / T 1040-2022, 1A type specimen test, and the test environment conditions are: 23°C, 50%RH; The Vicat softening point is tested according to GB / T 1633-2000, and the A120 test environment conditions are: 23°C, 50%RH; The Shore hardness test is carried out in accordance with GB / T 531, and the test environment conditions are: 23° C., 50% RH.
[0007] Furthermore, the mass ratio of the grafted and cross-linked vulcanized polyethylene composition as the dispersed phase to the grafted and non-cross-linked vulcanized polyethylene composition as the continuous phase is 1:(2-3).
[0008] Furthermore, the polyethylene resin includes one or more of high-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE).
[0009] Furthermore, the high-density polyethylene has a flow rate of 0.5-2.0 g / 10 min at a temperature of 190° C. and a load of 2.16 kg.
[0010] Furthermore, the linear low-density polyethylene has a flow rate of 0.5-2.0 g / 10 min at a temperature of 190° C. and a load of 2.16 kg.
[0011] Furthermore, the high-density polyethylene (HDPE) was purchased from Yanshan Petrochemical, with a grade of 5000S; Or purchased from Zhejiang Petrochemical, brand number 7260.
[0012] Furthermore, the linear low-density polyethylene (LLDPE) was purchased from Yanshan Petrochemical with a grade of 7042.
[0013] Furthermore, the boiling point of the silane coupling agent is 140-150°C.
[0014] Furthermore, the silane coupling agent is vinyl silane.
[0015] Furthermore, the silane coupling agent was purchased from Chenguang New Village with a brand number of 171.
[0016] Furthermore, the initiator is a di-25 liquid peroxide initiator.
[0017] Furthermore, the di-25 liquid peroxide initiator is 2,5-dimethyl-2,5-bishexane.
[0018] Furthermore, the initiator is purchased from Nouryon with a brand number of 101.
[0019] Furthermore, the antioxidant is a phosphite or hindered phenol antioxidant.
[0020] Furthermore, the antioxidant is antioxidant 168 and / or antioxidant 1010.
[0021] Furthermore, the antioxidant is purchased from BASF.
[0022] Furthermore, the water content of the liquid additive masterbatch is 70-75wt%.
[0023] Furthermore, the liquid additive masterbatch was purchased from Nanjing Xuzhi with a brand name of PW2070.
[0024] Furthermore, the nano zinc oxide was purchased from Weifang Aolong with a brand name of H01.
[0025] Furthermore, the catalyst is dioctyltin dilaurate.
[0026] Furthermore, the catalyst is purchased from Nouryon with the brand name TMG-216.
[0027] Furthermore, the stearic acid is purchased from Dukuda with a brand number of 1842.
[0028] The present invention also provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparing semi-finished product A: premixing a first polyethylene resin, a first silane coupling agent, an initiator, and a first antioxidant, and putting the premixed materials into a first twin-screw extruder for silane grafting reaction, extruding and granulating to obtain the semi-finished product A; Wherein, the semi-finished product A comprises a grafted uncrosslinked vulcanized polyethylene composition; Step 2, preparing semi-finished product B: premixing the semi-finished product A obtained in step 1 with a second polyethylene resin, a liquid additive masterbatch, and a second antioxidant, and putting the premixed semi-finished product A into a second twin-screw extruder for dynamic vulcanization, extrusion granulation, and obtaining the semi-finished product B; Wherein, the semi-finished product B comprises a grafted and cross-linked vulcanized polyethylene composition as a dispersed phase, and an ungrafted and uncross-linked vulcanized polyethylene composition as a continuous phase; Step 3, preparing finished product A: premixing the semi-finished product B prepared in step 2 with a second silane coupling agent, an initiator, and nano zinc oxide, and putting the premixed product into a third twin-screw extruder, subjecting the ungrafted and uncrosslinked vulcanized polyethylene composition in the semi-finished product B to a silane grafting reaction, and extruding and granulating to obtain the finished product A; The finished product A comprises a grafted and cross-linked vulcanized polyethylene composition as a dispersed phase, and a grafted and uncross-linked vulcanized polyethylene composition as a continuous phase; Step 4, preparing finished product B: high-density polyethylene (HDPE), catalyst, third antioxidant, and stearic acid are subjected to banburying, and after banburying, are put into a first single-screw extruder for dispersion and granulation to obtain the finished product B; Step 5, blending the finished product A in step 3 and the finished product B in step 4, and then putting them into a second single-screw extruder for extrusion to obtain the sealing strip coating material; The sealing strip coating material comprises a grafted and cross-linked vulcanized polyethylene composition as a dispersed phase, and a grafted and non-cross-linked vulcanized polyethylene composition as a continuous phase.
[0029] Furthermore, in step 1, the first polyethylene resin is a mixture of high-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE) in a mass ratio of 7:3.
[0030] Furthermore, in step 1, the first silane coupling agent is vinyl silane.
[0031] Furthermore, in step 1, the first antioxidant is a mixture of antioxidant 168 and antioxidant 1010, with a mass ratio of 1:1.
[0032] Furthermore, in step 1, the mass ratio of the first polyethylene resin, the first silane coupling agent, the initiator, and the first antioxidant is 5000:48.3:1.7:10.
[0033] Furthermore, the mixing rate of the premix in step 1 is 80 r / min, and the mixing time is 15 min.
[0034] Further, the processing temperature of each temperature zone of the first twin-screw extruder in step 1 is: 50-80°C in zone 1, 80-120°C in zone 2, 80-120°C in zone 3, 80-120°C in zone 4, 160-180°C in zone 5, 180-200°C in zone 6, 180-200°C in zone 7, 180-200°C in zone 8, 180-200°C in zone 9, 180-200°C in zone 10, and 170-190°C in zone 11; the head temperature is 170-190°C, the main engine speed is 450-700r / min, and the feeding speed is 50-80r / min.
[0035] Furthermore, the grafting in step 1 is that the peroxide in the initiator is thermally decomposed to generate highly active free radicals, and the free radicals capture hydrogen atoms in the polyethylene resin molecules, so that the polyethylene resin main chain carries active free radicals, which undergo a grafting reaction with a silane coupling agent containing double bonds, so that the silane group is grafted onto the polyethylene resin molecular chain.
[0036] Furthermore, in step 2, the second polyethylene resin is a mixture of high-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE) in a mass ratio of 5:2.
[0037] Furthermore, in step 2, the second antioxidant is a mixture of antioxidant 168 and antioxidant 1010, with a mass ratio of 1:1.
[0038] Furthermore, in step 2, the mass ratio of the semi-finished product A, the second polyethylene resin, the liquid additive masterbatch, and the second antioxidant is 1500:3500:(5-15):7.
[0039] Furthermore, the mixing rate of the premix in step 2 is 80 r / min and the mixing time is 5 min.
[0040] Further, the processing temperature of each temperature zone of the second twin-screw extruder in step 2 is: 50-80°C in zone 1, 50-80°C in zone 2, 50-80°C in zone 3, 80-100°C in zone 4, 160-200°C in zone 5, 160-200°C in zone 6, 160-200°C in zone 7, 160-200°C in zone 8, 160-200°C in zone 9, 160-200°C in zone 10, and 170-190°C in zone 11; the die head temperature is 170-190°C. The main engine speed is 550-700r / min, and the feeding speed is 40-60r / min.
[0041] Furthermore, the dynamic vulcanization in step 2 is as follows: the liquid additive masterbatch provides water to the semi-finished product A, so that the grafted and non-crosslinked vulcanized polyethylene composition in the semi-finished product A forms a three-dimensional crosslinked network structure of -Si-O-Si-, and the crosslinking vulcanization is completed. At the same time, the strong shearing action of the twin-screw extruder causes the grafted and crosslinked vulcanized polyethylene composition in the semi-finished product A to become micron-sized small particles, and the small particles are dispersed in the system for preparing the semi-finished product B in step 2, thereby realizing the process of vulcanization, shearing and dispersion.
[0042] Furthermore, in step 3, the mass ratio of the semi-finished product B, the second silane coupling agent, the initiator, and the nano zinc oxide is 4000:48.3:0.9:(8-16).
[0043] Further, in step 3, the processing temperature of each temperature zone of the third twin-screw extruder is: 50-80°C in zone 1, 80-120°C in zone 2, 80-120°C in zone 3, 80-120°C in zone 4, 160-180°C in zone 5, 180-200°C in zone 6, 180-200°C in zone 7, 180-200°C in zone 8, 180-200°C in zone 9, 180-200°C in zone 10, and 170-190°C in zone 11; the die head temperature is 170-190°C. The main engine speed is 450-700r / min, and the feeding speed is 50-80r / min.
[0044] Furthermore, in step 3, in a twin-screw extruder, the ungrafted and uncrosslinked vulcanized polyethylene composition as a continuous phase in the semi-finished product B is grafted with the second silane coupling agent, and the reaction principle is the same as that in step 1.
[0045] Furthermore, in step 4, the third antioxidant is a mixture of antioxidant 168 and antioxidant 1010, with a mass ratio of 1:1.
[0046] Furthermore, in step 4, the mass ratio of high-density polyethylene (HDPE), catalyst, third antioxidant and stearic acid is 4000:(28-42):8:400.
[0047] Furthermore, in step 4, the banburying temperature is 100-130° C., the banburying mixing rate is 90 r / min, and the mixing time is 5 min.
[0048] Furthermore, in step 4, the processing temperatures of each temperature zone of the first single screw extruder are: 80-120°C in zone 1, 160-200°C in zone 2, 160-200°C in zone 3, 160-200°C in zone 4, and 160-200°C in zone 5; the main engine speed is 50-60 r / min.
[0049] Furthermore, the internal mixing process in step 4 is to shear and heat the raw materials for preparing the finished product B, so that the raw materials are melted by heat to form an integrated mixture, and the integrated mixture is then put into the first single-screw extruder for dispersion and granulation.
[0050] Furthermore, in step 5, the mass ratio of finished product A to finished product B is 19:1.
[0051] Furthermore, in step 5, the processing temperatures of each temperature zone of the second single screw extruder are: 80-120°C in zone 1, 160-200°C in zone 2, 160-200°C in zone 3, 160-200°C in zone 4, and 160-200°C in zone 5; the main engine speed is 50-60 r / min.
[0052] Furthermore, the compositions of the first polyethylene resin and the second polyethylene resin are the same or different.
[0053] Furthermore, the compositions of the first silane coupling agent and the second silane coupling agent are the same or different.
[0054] Furthermore, the compositions of the first antioxidant, the second antioxidant and the third antioxidant are the same or different.
[0055] Furthermore, the equipment used for premixing is a mixer, and the equipment used for internal mixing is an internal mixer.
[0056] The present invention also provides a sealing strip, which is coated on a sealing strip substrate using the above-mentioned sealing strip coating material to obtain the sealing strip with the sealing strip coating; Among them, the thickness of the sealing strip coating is 0.2-0.4mm, and the maximum heat-resistant temperature is 260℃.
[0057] Furthermore, the coating is a frosted coating.
[0058] Furthermore, the sealing strip substrate is made of ethylene propylene diene monomer (EPDM).
[0059] The present invention also provides a method for preparing the above sealing strip, comprising the following steps: The ethylene propylene diene monomer rubber compound (EPDM compound) and the sealing strip coating material are respectively put into two single-screw extruders, and the two single-screw extruders extrude the two raw materials through the screw merging head respectively, and the sealing strip coating material is attached to the surface of the ethylene propylene diene monomer rubber compound. After extrusion, high-temperature vulcanization is performed to obtain the sealing strip.
[0060] Furthermore, the processing temperatures of each temperature zone of the single screw extruder into which the EPDM rubber compound (EPDM compound) is put are: 40-50°C in zone 1, 50-60°C in zone 2, 50-60°C in zone 3, 50-60°C in zone 4, 50-60°C in zone 5, and 50-60°C in zone 6; the main engine speed is 65r / min; the screw diameter is 45mm; the aspect ratio is 30; the main motor power is 7.5KW; and the maximum speed is 100rpm; The processing temperatures of each temperature zone of the single screw extruder into which the sealing strip coating material is put are: 150-165°C in zone 1, 165-180°C in zone 2, 165-180°C in zone 3, and 180-210°C in zone 4; the main engine speed is 4r / min; the screw diameter is 30mm; the aspect ratio is 20; the main motor power is 5KW; and the maximum speed is 100rpm; The temperature of the screw confluence head is 120°C; The extrusion speed is 10m / s; The high temperature vulcanization is performed online in a 60 m long oven, and the oven temperature is set at 230°C.
[0061] Furthermore, during extrusion and high-temperature vulcanization, stearic acid in the sealing strip coating material and zinc oxide as water-producing aids react as follows: 2C 17 H 35 COOH+4ZnO→2C 17 H 35 COOZn+2H2O+2Zn; The water produced by the reaction causes the grafted and uncrosslinked vulcanized polyethylene composition as the continuous phase in the sealing strip coating material to undergo crosslinking and vulcanization, adhere to the surface of the EPDM rubber compound, and undergo high-temperature setting.
[0062] Furthermore, the mass ratio of the ethylene propylene diene monomer rubber compound (EPDM compound) to the sealing strip coating material is (30-40):1.
[0063] The present invention further provides a vehicle sealing component, which comprises the above-mentioned sealing strip.
[0064] The beneficial effects of the present invention are: 1. The present invention provides a sealing strip coating material, wherein the raw materials include polyethylene resin, silane coupling agent, initiator, antioxidant, liquid additive masterbatch, nano zinc oxide, catalyst, and stearic acid, and grafting and / or crosslinking vulcanization reaction is performed to prepare the sealing strip coating material; through a specific preparation method, the ratio of the added raw materials and the order and proportion of the grafting and crosslinking vulcanization are adjusted, and the extrusion of the screw extruder is coordinated to construct a phase structure including a dispersed phase and a continuous phase; so that the crosslinking degree of the sealing strip coating material is 50.2-56.3%, the static friction coefficient is 0.16-0.29, the dynamic friction coefficient is 0.14-0.25, the tensile strength is 24.7-26.8MPa, the Vicat softening point is 124.3-127.9°C, and the Shore hardness is 61.4-61.9D; 2. The present invention changes the traditional process of preparing polyethylene coating materials by grafting and crosslinking vulcanization in one step to first implementing partial grafting, i.e., semi-finished product A, and then implementing crosslinking vulcanization of the grafted part, i.e., semi-finished product B, while introducing the remaining ungrafted raw materials, and then implementing grafting of the ungrafted part, i.e., finished product A, and then adding finished product B prepared from the remaining raw materials, blending finished product A and finished product B and then putting them into a second single-screw extruder for extrusion to obtain a sealing strip coating material including a polyethylene composition after grafting and crosslinking vulcanization as a dispersed phase and a polyethylene composition after grafting and non-crosslinking vulcanization as a continuous phase, and finally implementing crosslinking vulcanization of the continuous phase during the co-extrusion process of the sealing strip coating material and the sealing strip substrate, and thoroughly completing the grafting and crosslinking vulcanization of all raw materials, and designing a dynamic vulcanization preparation method, and the prepared sealing strip coating material has significantly improved impact strength, mechanical properties, heat resistance, corrosion resistance, creep resistance and stress cracking resistance; 3. In the sealing strip coating material, the grafted and cross-linked vulcanized polyethylene composition as the dispersed phase is in the form of micron-sized particles. After being extruded and attached to the sealing strip substrate along with the continuous phase, the sealing strip coating on the surface of the finally prepared sealing strip forms a slightly frosted state, so that the surface friction coefficient of the sealing strip is reduced by 15-30% compared with the surface friction coefficient of the sealing strip in the prior art, thereby reducing the abnormal noise generated by the car window using the sealing strip and improving the sealing performance; 4. In order to improve the heat resistance of the sealing strip coating attached to the sealing strip and avoid the melting of the coating during the EPDM sealing strip jointing process, the present invention specifically selects a high temperature environment, so that stearic acid and zinc oxide are used as water-producing additives to chemically react to produce water, so that the continuous phase in the sealing strip coating material and the sealing strip substrate are cross-linked and vulcanized in the sealing strip coating material during the extrusion coating process, thereby solving the problem of temperature difference resistance of polyethylene coating materials in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1This is a sample picture after the sealing strip substrate is coated with the sealing strip coating material of the present invention. DETAILED DESCRIPTION
[0066] Examples 1-8 are sealing strip coating materials and preparation methods thereof. Examples 9-11 are sealing strips prepared using the sealing strip coating materials in the examples.
[0067] Wherein, the testing method of the sealing strip material performance is as follows: The crosslinking degree is tested according to GB / T 18474-2001, and the test environment conditions are: 23°C, 50%RH (relative humidity); The dynamic friction coefficient is tested according to GB / T 21282-2007, and the test environment conditions are: 23°C, 50%RH; The static friction coefficient is tested according to GB / T 21282-2007, and the test environment conditions are: 23°C, 50%RH; The tensile strength is tested according to GB / T 1040-2022, 1A type specimen test, and the test environment conditions are: 23°C, 50%RH; The Vicat softening point is tested according to GB / T 1633-2000, and the A120 test environment conditions are: 23°C, 50%RH; The Shore hardness test is carried out in accordance with GB / T 531, and the test environment conditions are: 23° C., 50% RH.
[0068] Example 1 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die head temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 10g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the head temperature was 190℃. The main engine speed was 700r / min, the feeding speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 8g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg high-density polyethylene (HDPE) (brand 7260 Zhejiang Petrochemical), 40 g catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g antioxidant 168 (BASF) and 4 g antioxidant 1010 (BASF), 0.4 kg stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130 ° C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80 ° C in zone 1, 160 ° C in zone 2, 200 ° C in zone 3, 200 ° C in zone 4, and 160 ° C in zone 5; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and put into a second single-screw extruder for extrusion, and the processing temperature of each temperature zone is: 80°C in zone 1, 200°C in zone 2, 200°C in zone 3, 160°C in zone 4, and 160°C in zone 5; the main engine speed is 50r / min, and the sealing strip coating material is obtained.
[0069] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 53.6%, a static friction coefficient of 0.16, a dynamic friction coefficient of 0.14, a tensile strength of 25.1 MPa, a Vicat softening point of 126.3° C., and a Shore hardness of 61.7D.
[0070] Example 2 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 5g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the die head temperature was 190℃. The main engine speed was 700r / min, the feed speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 8g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg high-density polyethylene (HDPE) (brand 7260 Zhejiang Petrochemical), 40 g catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g antioxidant 168 (BASF) and 4 g antioxidant 1010 (BASF), 0.4 kg stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130 ° C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80 ° C in zone 1, 160 ° C in zone 2, 200 ° C in zone 3, 200 ° C in zone 4, and 160 ° C in zone 5; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and then put into a second single-screw extruder for extrusion. The processing temperatures in each temperature zone are: 120°C in zone 1, 160°C in zone 2, 160°C in zone 3, 200°C in zone 4, and 200°C in zone 5; the main engine speed is 60r / min, and the sealing strip coating material is obtained.
[0071] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 51.9%, a static friction coefficient of 0.29, a dynamic friction coefficient of 0.25, a tensile strength of 24.7 MPa, a Vicat softening point of 124.3° C., and a Shore hardness of 61.5D.
[0072] Example 3 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 15g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the head temperature was 190℃. The main engine speed was 700r / min, the feed speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 8g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg high-density polyethylene (HDPE) (brand 7260 Zhejiang Petrochemical), 40 g catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g antioxidant 168 (BASF) and 4 g antioxidant 1010 (BASF), 0.4 kg stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130 ° C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80 ° C in zone 1, 160 ° C in zone 2, 200 ° C in zone 3, 200 ° C in zone 4, and 160 ° C in zone 5; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and put into a second single-screw extruder for extrusion. The processing temperatures in each temperature zone are: 80°C in zone 1, 160°C in zone 2, 200°C in zone 3, 200°C in zone 4, and 160°C in zone 5; the main engine speed is 50r / min, and the sealing strip coating material is obtained.
[0073] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 55.9%, a static friction coefficient of 0.18, a dynamic friction coefficient of 0.17, a tensile strength of 25.9 MPa, a Vicat softening point of 127.9° C., and a Shore hardness of 61.8D.
[0074] Example 4 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 10g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the head temperature was 190℃. The main engine speed was 700r / min, the feeding speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 12g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg high-density polyethylene (HDPE) (brand 7260 Zhejiang Petrochemical), 40 g catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g antioxidant 168 (BASF) and 4 g antioxidant 1010 (BASF), 0.4 kg stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130 ° C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80 ° C in zone 1, 160 ° C in zone 2, 200 ° C in zone 3, 200 ° C in zone 4, and 160 ° C in zone 5; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and put into a second single-screw extruder for extrusion, and the processing temperatures in each temperature zone are: 80°C in zone 1, 200°C in zone 2, 160°C in zone 3, 200°C in zone 4, and 160°C in zone 5; the main engine speed is 50r / min, and the sealing strip coating material is obtained.
[0075] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 54.6%, a static friction coefficient of 0.17, a dynamic friction coefficient of 0.16, a tensile strength of 26.4 MPa, a Vicat softening point of 126.8° C., and a Shore hardness of 61.5D.
[0076] Example 5 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 10g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the head temperature was 190℃. The main engine speed was 700r / min, the feeding speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 16g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg high-density polyethylene (HDPE) (brand 7260 Zhejiang Petrochemical), 40 g catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g antioxidant 168 (BASF) and 4 g antioxidant 1010 (BASF), 0.4 kg stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130 ° C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80 ° C in zone 1, 160 ° C in zone 2, 200 ° C in zone 3, 200 ° C in zone 4, and 160 ° C in zone 5; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and then put into a second single-screw extruder for extrusion. The processing temperatures in each temperature zone are: 80°C in zone 1, 200°C in zone 2, 200°C in zone 3, 200°C in zone 4, and 200°C in zone 5; the main engine speed is 60r / min, and the sealing strip coating material is obtained.
[0077] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 55.7%, a static friction coefficient of 0.23, a dynamic friction coefficient of 0.20, a tensile strength of 26.5 MPa, a Vicat softening point of 127.1° C., and a Shore hardness of 61.5D.
[0078] Example 6 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 10g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the head temperature was 190℃. The main engine speed was 700r / min, the feeding speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 8g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg of high-density polyethylene (HDPE) (brand 7260 Zhejiang Petrochemical), 28 g of catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g of antioxidant 168 (BASF) and 4 g of antioxidant 1010 (BASF), and 0.4 kg of stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130°C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80°C in zone 1, 160°C in zone 2, 200°C in zone 3, 200°C in zone 4, and 160°C in zone 5; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and put into a second single-screw extruder for extrusion, and the processing temperature of each temperature zone is: 80°C in zone 1, 200°C in zone 2, 200°C in zone 3, 160°C in zone 4, and 160°C in zone 5; the main engine speed is 50r / min, and the sealing strip coating material is obtained.
[0079] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 51.3%, a static friction coefficient of 0.28, a dynamic friction coefficient of 0.24, a tensile strength of 24.9 MPa, a Vicat softening point of 125.3° C., and a Shore hardness of 61.7D.
[0080] Example 7 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die head temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 10g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the head temperature was 190℃. The main engine speed was 700r / min, the feeding speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 8g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg of high-density polyethylene (HDPE) (brand 7260 Zhejiang Petrochemical), 42 g of catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g of antioxidant 168 (BASF) and 4 g of antioxidant 1010 (BASF), and 0.4 kg of stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130°C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80°C in zone 1, 160°C in zone 2, 200°C in zone 3, 200°C in zone 4, and 160°C in zone 5; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and put into a second single-screw extruder for extrusion, and the processing temperatures in each temperature zone are: 100°C in zone 1, 200°C in zone 2, 160°C in zone 3, 160°C in zone 4, and 160°C in zone 5; the main engine speed is 50r / min, and the sealing strip coating material is obtained.
[0081] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 56.3%, a static friction coefficient of 0.23, a dynamic friction coefficient of 0.20, a tensile strength of 26.2 MPa, a Vicat softening point of 126.8° C., and a Shore hardness of 61.4D.
[0082] Example 8 This embodiment provides a method for preparing a sealing strip coating material, comprising the following steps: Step 1, preparation of semi-finished product A: 3.5 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 1.5 kg linear low-density polyethylene (LLDPE) (brand 7042 Yanshan Petrochemical), 48.3 g first silane coupling agent (brand 171 Chenguang New Village), 1.7 g initiator (brand 101 Nouryon), 5g antioxidant 168 (BASF) and 5g antioxidant 1010 (BASF) are placed in a mixer for premixing at a premixing rate of 80r / min and a mixing time of 5min. After premixing, they are put into the first twin-screw extruder for silane grafting reaction. The processing temperatures of each temperature zone of the first twin-screw extruder are: 50°C in zone 1, 80°C in zone 2, 80°C in zone 3, 80°C in zone 4, 160°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, 180°C in zone 10, and 170°C in zone 11; the die head temperature is 170°C, the main engine speed is 450r / min, and the feed speed is 50r / min. Extrusion granulation to obtain the semi-finished product A; Step 2, preparation of semi-finished product B: 1.5 kg of semi-finished product A obtained in step 1, 2.5 kg of high-density polyethylene (HDPE) (grade 5000S Yanshan Petrochemical), 1.0 kg of linear low-density polyethylene (LLDPE) (grade 7042 Yanshan Petrochemical), 10g liquid additive masterbatch (brand PW2070 Nanjing Xuzhi), 3.5g antioxidant 168 (BASF) and 3.5g antioxidant 1010 (BASF) were placed in a mixer for premixing, the premixing rate was 80r / min, the mixing time was 5min, and after premixing, they were put into the second twin-screw extruder for dynamic vulcanization. The processing temperatures of each temperature zone of the second twin-screw extruder were: 80℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 100℃ in zone 4, 200℃ in zone 5, 200℃ in zone 6, 200℃ in zone 7, 200℃ in zone 8, 200℃ in zone 9, 200℃ in zone 10, and 190℃ in zone 11; the head temperature was 190℃. The main engine speed was 700r / min, the feeding speed was 60r / min, and the semi-finished product B was obtained by extrusion granulation; Step 3, preparing finished product A: premix 4kg of the semi-finished product B prepared in step 2 with 48.3g of the second silane coupling agent (brand 171 Chenguang New Village), 0.9g of the initiator (brand 101 Nouryon), and 8g of nano zinc oxide (brand H01 Weifang Aolong) through a mixer, and place them in the mixer for premixing. The premixing rate is 80r / min, the mixing time is 5min, and after premixing, it is put into the third twin-screw extruder. The processing temperatures of each temperature zone of the third twin-screw extruder are: zone 1 80°C, zone 2 80°C, zone 3 120°C, zone 4 120°C, zone 5 160°C, zone 6 180°C, zone 7 200°C, zone 8 200°C, zone 9 200°C, zone 10 180°C, zone 11 170-190°C; the head temperature is 170°C. The main engine speed is 450r / min, the feeding speed is 80r / min, and the extrusion granulation is performed to obtain the finished product A; Step 4, preparing finished product B: 4 kg high-density polyethylene (HDPE) (brand 5000S Yanshan Petrochemical), 42 g catalyst dioctyltin dilaurate (brand TMG-216 Nouryon), 4 g antioxidant 168 (BASF) and 4 g antioxidant 1010 (BASF), 0.4 kg stearic acid (brand 1842 Dukuda) are placed in an internal mixer for internal mixing, the internal mixing temperature is 100-130 ° C, the mixing rate of the internal mixing is 90 r / min, the mixing time is 15 min, and after internal mixing, it is put into the first single-screw extruder for dispersion and granulation. The processing temperatures of each temperature zone of the first single-screw extruder are: 80 ° C in the first zone, 160 ° C in the second zone, 200 ° C in the third zone, 200 ° C in the fourth zone, and 160 ° C in the fifth zone; the main engine speed is 60 r / min, and the finished product B is obtained; Step 5, the finished product A in step 3 and the finished product B in step 4 are blended in a mass ratio of 19:1 and then put into a second single-screw extruder for extrusion. The processing temperatures in each temperature zone are: 100°C in zone 1, 190°C in zone 2, 200°C in zone 3, 180°C in zone 4, and 160°C in zone 5; the main engine speed is 50r / min, and the sealing strip coating material is obtained.
[0083] The performance of the sealing strip coating material prepared in this embodiment was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 50.2%, a static friction coefficient of 0.24, a dynamic friction coefficient of 0.21, a tensile strength of 26.8 MPa, a Vicat softening point of 126.3° C., and a Shore hardness of 61.9D.
[0084] Example 9 This embodiment provides a sealing strip, wherein the sealing strip substrate is coated with the sealing strip coating material in Embodiment 1 to obtain the sealing strip with the sealing strip coating; The thickness of the sealing strip coating is 0.3 mm, and the maximum heat-resistant temperature is 260°C.
[0085] In this embodiment, the coating is a frosted coating.
[0086] The sealing strip substrate is made of ethylene propylene diene monomer (EPDM).
[0087] The preparation method of the sealing strip comprises the following steps: putting ethylene propylene diene monomer rubber compound (EPDM compound) and sealing strip coating material into two single-screw extruders at a mass ratio of 30:1 respectively, the two single-screw extruders respectively extrude the two raw materials through a screw converging die head to attach the sealing strip coating material to the surface of the ethylene propylene diene monomer rubber compound, and vulcanizing at high temperature after extrusion to obtain the sealing strip; Figure 1 As shown, the side that contacts the vehicle glass is coated with the sealing strip coating, and it can be seen that its surface is a frosted coating, and the side that does not contact the vehicle glass is not coated with the sealing strip coating, and it can be seen that its surface is nearly smooth.
[0088] Specifically, the processing temperatures of each temperature zone of the single screw extruder into which the EPDM compound is put are: 40°C in zone 1, 50°C in zone 2, 50°C in zone 3, 50°C in zone 4, 50°C in zone 5, and 50°C in zone 6; the main engine speed is 65r / min; the screw diameter is 45mm; the aspect ratio is 30; the main motor power is 7.5KW; and the maximum speed is 100rpm; The processing temperatures of each temperature zone of the single screw extruder into which the sealing strip coating material is put are: 165°C in zone 1, 165°C in zone 2, 165°C in zone 3, and 180°C in zone 4; the main engine speed is 4r / min; the screw diameter is 30mm; the aspect ratio is 20; the main motor power is 5KW; and the maximum speed is 100rpm; The temperature of the screw confluence head is 120°C; The extrusion speed is 10m / s; The high temperature vulcanization is performed online in a 60 m long oven, and the oven temperature is set at 230°C.
[0089] Example 10 This embodiment provides a sealing strip, wherein the sealing strip substrate is coated with the sealing strip coating material in embodiment 4 to obtain the sealing strip with the sealing strip coating; The thickness of the sealing strip coating is 0.2 mm, and the maximum heat-resistant temperature is 260°C.
[0090] In this embodiment, the coating is a frosted coating.
[0091] The sealing strip substrate is made of ethylene propylene diene monomer (EPDM).
[0092] The preparation method of the sealing strip comprises the following steps: putting ethylene propylene diene monomer rubber compound (EPDM compound) and sealing strip coating material into two single-screw extruders at a mass ratio of 35:1, respectively, the two single-screw extruders respectively extrude the two raw materials through a screw converging die head to attach the sealing strip coating material to the surface of the ethylene propylene diene monomer rubber compound, and vulcanizing at high temperature after extrusion to obtain the sealing strip; Specifically, the processing temperatures of each temperature zone of the single screw extruder into which the EPDM rubber compound (EPDM compound) is put are: 50°C in zone 1, 60°C in zone 2, 60°C in zone 3, 60°C in zone 4, 60°C in zone 5, and 50°C in zone 6; the main engine speed is 65r / min; the screw diameter is 45mm; the aspect ratio is 30; the main motor power is 7.5KW; and the maximum speed is 100rpm; The processing temperatures of each temperature zone of the single screw extruder into which the sealing strip coating material is put are: 150°C in zone 1, 180°C in zone 2, 180°C in zone 3, and 210°C in zone 4; the main engine speed is 4r / min; the screw diameter is 30mm; the aspect ratio is 20; the main motor power is 5KW; and the maximum speed is 100rpm; The temperature of the screw confluence head is 120°C; The extrusion speed is 10m / s; The high temperature vulcanization is performed online in a 60 m long oven, and the oven temperature is set at 230°C.
[0093] Embodiment 11 This embodiment provides a sealing strip, wherein the sealing strip substrate is coated with the sealing strip coating material in Embodiment 8 to obtain the sealing strip with the sealing strip coating; The thickness of the sealing strip coating is 0.4 mm, and the maximum heat-resistant temperature is 260°C.
[0094] In this embodiment, the coating is a frosted coating.
[0095] The sealing strip substrate is made of ethylene propylene diene monomer (EPDM).
[0096] The preparation method of the sealing strip comprises the following steps: putting ethylene propylene diene monomer rubber compound (EPDM compound) and sealing strip coating material into two single-screw extruders at a mass ratio of 40:1, respectively, the two single-screw extruders respectively extrude the two raw materials through a screw converging die head to attach the sealing strip coating material to the surface of the ethylene propylene diene monomer rubber compound, and vulcanizing at high temperature after extrusion to obtain the sealing strip; Specifically, the processing temperatures of each temperature zone of the single screw extruder into which the EPDM rubber compound (EPDM compound) is put are: 40°C in zone 1, 60°C in zone 2, 60°C in zone 3, 60°C in zone 4, 60°C in zone 5, and 60°C in zone 6; the main engine speed is 65r / min; the screw diameter is 45mm; the aspect ratio is 30; the main motor power is 7.5KW; and the maximum speed is 100rpm; The processing temperatures of each temperature zone of the single screw extruder into which the sealing strip coating material is put are: 150°C in zone 1, 180°C in zone 2, 180°C in zone 3, and 210°C in zone 4; the main engine speed is 4r / min; the screw diameter is 30mm; the aspect ratio is 20; the main motor power is 5KW; and the maximum speed is 100rpm; The temperature of the screw confluence head is 120°C; The extrusion speed is 10m / s; The high temperature vulcanization is performed online in a 60 m long oven, and the oven temperature is set at 230°C.
[0097] Comparative Example 1 This comparative example adopts the one-step cross-linking grafting method in the prior art to prepare the sealing strip coating material, and the specific steps are as follows: 3.42 kg of high-density polyethylene (HDPE) (brand 5000S, Yanshan Petrochemical), 1.47 kg of linear low-density polyethylene (LLDPE) (brand 7042, Yanshan Petrochemical), 5 g of antioxidant 168 (BASF) and 5 g of antioxidant 1010 (BASF), and 100 g of silicone masterbatch (brand MB50, Dow) were placed in a mixer for premixing at a rate of 80 r / min, mixing time is 5min, after premixing, put into the twin-screw extruder for silane grafting reaction, the processing temperature of each temperature zone of the twin-screw extruder is: 50℃ in zone 1, 80℃ in zone 2, 80℃ in zone 3, 80℃ in zone 4, 160℃ in zone 5, 180℃ in zone 6, 180℃ in zone 7, 180℃ in zone 8, 180℃ in zone 9, 180℃ in zone 10, 170℃ in zone 11; the head temperature is 170℃, the main engine speed is 450r / min, and the feeding speed is 50r / min. Extrusion granulation to obtain the sealing strip coating material in this comparative example; Among them, silicone masterbatch MB50 is used as a lubricant to reduce the surface friction coefficient and is an indispensable additive in the prior art.
[0098] The performance of the sealing strip coating material prepared in this comparative example was tested, and the test results are as follows: The sealing strip coating material has a cross-linking degree of 0%, a static friction coefficient of 0.31, a dynamic friction coefficient of 0.28, a tensile strength of 20.4 MPa, a Vicat softening point of 91.3° C., and a hardness of 56 degrees.
[0099] The performance of the sealing strip coating materials in Examples 1-8 and Comparative Example 1 is compared, and the comparison results are shown in Table 1: Table 1 Performance test results of sealing strip coating materials of Examples 1-8 and Comparative Example 1
[0100] By comparison, it can be seen that the present invention changes the traditional process of preparing polyethylene coating materials by grafting and cross-linking vulcanization in one step to first realizing partial grafting, that is, semi-finished product A, and while introducing the remaining ungrafted raw materials, realizing cross-linking vulcanization of the first grafted part, that is, semi-finished product B, and then realizing grafting of the ungrafted part, that is, finished product A, and then adding finished product B prepared by the remaining raw materials, and mixing finished product A and finished product B and putting them into a second single-screw extruder for extrusion to obtain a sealing strip coating material including a polyethylene composition after grafting and cross-linking vulcanization as a dispersed phase, and a polyethylene composition after grafting and non-cross-linking vulcanization as a continuous phase. Finally, in the process of co-extrusion of the sealing strip coating material and the sealing strip substrate, cross-linking vulcanization of the continuous phase is realized, and the grafting and cross-linking vulcanization of all raw materials are completely completed. A dynamic vulcanization preparation method is designed, and the impact strength, mechanical properties, heat resistance, corrosion resistance, creep resistance and stress cracking resistance of the prepared sealing strip coating material are significantly improved compared with the polyethylene coating material prepared by grafting and cross-linking vulcanization in one step in the prior art.
[0101] It should be understood that the present invention is not limited to what has been described above and shown in the accompanying drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A sealing strip coating material, characterized in that: The raw materials include polyethylene resin, silane coupling agent, initiator, antioxidant, liquid additive masterbatch, nano zinc oxide, catalyst, stearic acid, and grafting and / or crosslinking vulcanization reaction is carried out to prepare the sealing strip coating material; The sealing strip coating material comprises a grafted and cross-linked vulcanized polyethylene composition as a dispersed phase, and a grafted and uncross-linked vulcanized polyethylene composition as a continuous phase; The sealing strip coating material has a crosslinking degree of 50.2-56.3%, a static friction coefficient of 0.16-0.29, a dynamic friction coefficient of 0.14-0.25, a tensile strength of 24.7-26.8 MPa, a Vicat softening point of 124.3-127.9° C., and a Shore hardness of 61.4-61.9D.
2. The sealing strip coating material according to claim 1, characterized in that: The polyethylene resin includes one or more of high-density polyethylene and linear low-density polyethylene; The silane coupling agent is vinyl silane; The water content of the liquid additive masterbatch is 70-75wt%; The catalyst is dioctyltin dilaurate.
3. A method for preparing the sealing strip coating material according to any one of claims 1 to 2, characterized in that: The steps include: Step 1, preparing semi-finished product A: premixing a first polyethylene resin, a first silane coupling agent, an initiator, and a first antioxidant, and putting the premixed materials into a first twin-screw extruder for silane grafting reaction, extruding and granulating to obtain the semi-finished product A; Step 2, preparing semi-finished product B: premixing the semi-finished product A obtained in step 1 with a second polyethylene resin, a liquid additive masterbatch, and a second antioxidant, and putting the premixed semi-finished product A into a second twin-screw extruder for dynamic vulcanization, extrusion granulation, and obtaining the semi-finished product B; Step 3, preparing finished product A: premixing the semi-finished product B prepared in step 2 with the second silane coupling agent, the initiator, and nano zinc oxide, and putting the premixed semi-finished product B into a third twin-screw extruder for extrusion granulation to obtain the finished product A; Step 4, preparing finished product B: mixing high-density polyethylene, a catalyst, a third antioxidant, and stearic acid, and then putting them into a first single-screw extruder for dispersion and granulation to obtain the finished product B; Step 5: blend the finished product A in step 3 and the finished product B in step 4, and then put them into a second single-screw extruder for extrusion to obtain the sealing strip coating material.
4. The method for preparing the sealing strip coating material according to claim 3, characterized in that: The compositions of the first polyethylene resin and the second polyethylene resin are the same or different; The compositions of the first silane coupling agent and the second silane coupling agent are the same or different; The compositions of the first antioxidant, the second antioxidant and the third antioxidant are the same or different.
5. The method for preparing the sealing strip coating material according to claim 3, characterized in that: The equipment used for premixing is a mixer, and the equipment used for internal mixing is an internal mixer.
6. A sealing strip, characterized in that: Using the sealing strip coating material according to any one of claims 1 to 2 to coat a sealing strip substrate to obtain the sealing strip; Among them, the thickness of the sealing strip coating is 0.2-0.4mm, and the maximum heat-resistant temperature is 260℃.
7. The sealing strip according to claim 6, characterized in that: The sealing strip substrate is made of EPDM rubber.
8. A method for preparing a sealing strip according to any one of claims 6 to 7, characterized in that: The steps include: The EPDM rubber compound and the sealing strip coating material are respectively put into two single-screw extruders, and the two single-screw extruders extrude the two raw materials through the screw merging head respectively, and the sealing strip coating material is attached to the surface of the EPDM rubber compound. After extrusion, high-temperature vulcanization is performed to obtain the sealing strip.
9. The method for preparing the sealing strip according to claim 8, characterized in that: The processing temperatures of the single screw extruder in each temperature zone of the EPDM rubber compound are: 40-50°C in zone 1, 50-60°C in zone 2, 50-60°C in zone 3, 50-60°C in zone 4, 50-60°C in zone 5, and 50-60°C in zone 6; the main engine speed is 65r / min; the screw diameter is 45mm; the aspect ratio is 30; the main motor power is 7.5KW; and the maximum speed is 100rpm; The processing temperatures of each temperature zone of the single screw extruder into which the sealing strip coating material is put are: 150-165°C in zone 1, 165-180°C in zone 2, 165-180°C in zone 3, and 180-210°C in zone 4; the main engine speed is 4r / min; the screw diameter is 30mm; the aspect ratio is 20; the main motor power is 5kW; and the maximum speed is 100rpm; The temperature of the screw confluence head is 120°C; The extrusion speed is 10m / s; The high temperature vulcanization is performed online in a 60 m long oven, and the oven temperature is set at 230°C.
10. A sealing component for a vehicle, characterized in that: The vehicle sealing component comprises the sealing strip according to any one of claims 6-7.
Citation Information
Patent Citations
The coating material for car weatherstrip and aprocess for preparing the same
KR100644256B1
Graft modified polyethylene anti-wear and enhanced EPDM rubber sealing strip
CN106046568A
Preparation method of organosilane crosslinked polyethylene by two-step method
CN107674155A
Two-step method for preparing silane naturally crosslinked polyethylene
CN107936441A
Vehicle door and window sealing strip with ethylene coating and its formation process
CN1526579A
